2021
DOI: 10.3390/nu13103622
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviour among University Students: Relationships with Age, Socioeconomic Status, Physical Activity, Body Mass Index, Waist-to-Height Ratio and Social Desirability

Abstract: Eating behaviour is of particular interest for research focusing on body weight status. However, little is known about the relationships of certain factors, especially social desirability, with self-reported eating behaviour such as cognitive restraint, uncontrolled eating, and emotional eating among young adult males and females. This study aimed to evaluate the relationships between eating behaviour and age, socioeconomic status (SES), physical activity (PA), body mass index (BMI), waist-to-height ratio (WHt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 31 publications
6
32
0
Order By: Relevance
“…Females tended to have a higher EBS-SF score, which was more significant in Eastern China in the stepwise regression stratified by region. Other studies found that emotional eating and uncontrolled eating were positively correlated in females and that women were much more vulnerable to various eating disorders, which was consistent with our results [50][51][52][53]. Therefore, females are supposed to pay more attention to healthy eating behavior.…”
Section: Sexsupporting
confidence: 91%
See 1 more Smart Citation
“…Females tended to have a higher EBS-SF score, which was more significant in Eastern China in the stepwise regression stratified by region. Other studies found that emotional eating and uncontrolled eating were positively correlated in females and that women were much more vulnerable to various eating disorders, which was consistent with our results [50][51][52][53]. Therefore, females are supposed to pay more attention to healthy eating behavior.…”
Section: Sexsupporting
confidence: 91%
“…The residents aged 26-35 in the central region were more likely to have higher EBS-SF scores in this study. The younger residents may behave worse in eating because of lower inhibitory control, higher reward sensitivity, and higher pleasure-seeking, as it was shown in the research that young adults starting independent life were more vulnerable to developing unhealthy eating habits [51,56]. A study showed that older people would consume more fruits and vegetables than younger adults, and consume more fruits and vegetables instead of high-fat food, which was beneficial to health [57].…”
Section: Agementioning
confidence: 98%
“…A few interesting studies in young Poles have recently been published, including papers on eating behaviors among university students [ 25 ], eating habits and body composition of young Poles [ 26 ], and international studies on eating disorders, involving Polish samples [ 27 , 28 ]. However, the current body of evidence in the field of eating behaviors, diet, and physical activity among emerging adults in Poland and Central Europe is still scarce and more data are needed to develop preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies by other authors highlight changes in women’s body image associated with increased BMI as a factor of restrictive, non-physiological dietary changes aimed at excessive weight reduction after pregnancy instead of implementing a balanced dietary model with reduced stressors before and during pregnancy. Body mass index is a predictor for the patho-mechanism of eating relationship disorders translating into perceived body image in extreme clinical cases of dysmorphophobia among postpartum women [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%